Pemanfaatan Kolase Sebagai Alat Pembelajaran Untuk Meningkatkan Keterampilan Motorik Halus Anak Di Sekolah Dasar - Nur Kholifah, Reza; Nuzsep Almigo (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
Early childhood is a child in the golden period, also known as the "Golden Age", during which the growth and development of children in various aspects develops rapidly. Children at an early age are in dire need of stimulation appropriate to their age and abilities: infants (0-1 years), toddlers (2-3 years), playgroups (3-6 years), and early school age (6-8 years). Children's fine motor skills are greatly influenced by the making of this collage. The author uses the method of playing while learning by tearing origami paper and pasting it on the given paper. The purpose of this study was to find out whether children's fine motor development improved when they participated in collage activities with various materials and tools such as glue, origami, and making pictures with patterns. This study strives to help children become more innovative and creative. The author uses a qualitative descriptive method which is this method to collect information